EDUKASI STOP BULLYING PADA ANAK - Naili Sa'ida; Tri Kurnuawati; Holy Ichda Wahyuni (PeKA: Jurnal Pengabdian Kepada Masyarakat, 2022)
ABSTRACTThis study aims to educate children not to bully their friends or those around them. The research method used in this research is qualitative. Data collection techniques using documentation, interviews and observations. Data analysis using triangulation technique. The results showed that with stop bullying education, children were able to introduce children to the types of bullying, children were also able to know that bullying is an act that harms others, and children know the impact of bullying